2014
DOI: 10.5489/cuaj.1665
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of patients with biochemical relapse after radical prostatectomy treated with androgen deprivation: Castration-resistance influential factors

Abstract: In BCR patients treated with ADT, the median to CR was 14 years. PSA-DT <6 months, PSA velocity (ng/mL/year) and seminal vesicle involvement were influential variables. From the CR, the median time to death was 3.2 years. Ki-67 marker was an independent influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In our study, PSAV, PSADT, and Gleason score were not independently associated with survival endpoints. On the other hand, several studies have recommended that these parameters be utilized to decide on the timing of ADT at PSA-recurrence following RP [19][20][21][22][23][24][25][26][27][28][29]. Van den Bergh, et al reported in a systematic review that early ADT cannot be recommended as the standard-of-care in the setting of PSA recurrence or local recurrence, and that ADT should be reserved for patients with the highest risk of disease progression, defined as short PSADT of less than 6-12 months or Gleason score of greater than 8 [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, PSAV, PSADT, and Gleason score were not independently associated with survival endpoints. On the other hand, several studies have recommended that these parameters be utilized to decide on the timing of ADT at PSA-recurrence following RP [19][20][21][22][23][24][25][26][27][28][29]. Van den Bergh, et al reported in a systematic review that early ADT cannot be recommended as the standard-of-care in the setting of PSA recurrence or local recurrence, and that ADT should be reserved for patients with the highest risk of disease progression, defined as short PSADT of less than 6-12 months or Gleason score of greater than 8 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Van den Bergh, et al reported in a systematic review that early ADT cannot be recommended as the standard-of-care in the setting of PSA recurrence or local recurrence, and that ADT should be reserved for patients with the highest risk of disease progression, defined as short PSADT of less than 6-12 months or Gleason score of greater than 8 [21]. Algarra, et al reported seminal vesical involvement and PSAV of greater than 0.84 ng/mL/year, in addition to PSADT, to be adverse features associated with disease progression in patients who received ADT at PSA recurrence [22]. In a cohort of patients with mainly high-risk disease, faster PSADT, higher Gleason score, and early intervention were associated with a lower risk of CSS [25].…”
Section: Discussionmentioning
confidence: 99%
“… 20 21 22 23 25 26 27 28 29 30 Van den Bergh, et al 22 reported in a systematic review that early ADT cannot be recommended as the standard-of-care for PSA recurrence or local recurrence, and that ADT should be reserved for patients with the highest risk of disease progression, defined as short PSADT of less than 6–12 months or Gleason score of greater than 8. Algarra, et al 23 reported seminal vesical involvement, PSAV of greater than 0.84 ng/mL/year, and PSADT to be considered as adverse features associated with disease progression in patients who received ADT at PSA recurrence. In a cohort of patients with mainly high-risk disease, faster PSADT, higher Gleason score, and early intervention were associated with a lower risk of CSS.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer (PCa) is one of the most prevalent cancer types in men; in 2015, there were 60,300 newly diagnosed cases of PCa in China, resulting in 26,000 mortalities ( 1 ). Disease recurrence has been reported in a large proportion of patients following radical prostatectomy ( 2 ), and castration-resistant disease typically develops as a result ( 3 , 4 ). Although prognostic and clinical indicators were implemented, the prognostic effect was not fully understood ( 5 ).…”
Section: Introductionmentioning
confidence: 99%